Spannungseinprägende aktive Filter zur Kompensation der Stromverzerrungen von Netzstromrichtern - Bernet, Daniel (KIT Scientific Publishing, 2023)
In this thesis, the use of voltage-source active filters for harmonic mitigation of grid-connected power converters is proposed. Based on a modeling of this novel converter configuration, an operating strategy is derived to accomplish this task with low control bandwith, low passive filtering effort, and high efficiency with only a small increase in installed semiconductor power.